View from White Pass and Yukon Railway passenger car - Swanberg, J. W. (Jack W.), 1939- (Creator) (1977)
White Pass & Yukon Railway Train No. 6, crossing trestle near White Pass, Alaska. Looking back along train, showing ten coaches. Archives & Special Collections at the Thomas J. Dodd Research Center, University of Connecticut Library J.W. Swanberg Papers